Future smart battery and management: Advanced sensing from external to embedded multi-dimensional measurement - Wei, Zhongbao; Zhao, Jiyun; He, Hongwen; Ding, Guanglin; Cui, Haoyong; Liu, Longcheng (Journal of power sources, 2021)
Lithium-ion batteries (LIBs) has seen widespread applications in a variety of fields like the renewable penetration, electrified transportation, and portable electronics. A reliable battery management system (BMS) is critical to fulfill the expectations on the reliability, efficiency and longevity of LIB systems. Recent research progresses have witnessed the emerging technique of smart battery and the associated management system, which can potentially overcome the deficiencies met by traditional BMSs. Motivated by this, this paper reviews the research progresses on the smart cell and smart battery system from multiple aspects, including the system design, sensing techniques, and the potential innovation of system integration. The transition from conventional LIB system towards higher smartness and the incurred advantages/challenges are overviewed. Special focuses are given to the existing and emerging cell-level, multi-dimensional (electro-mechanical-thermal) sensing techniques that may play critical roles in the management of smart cells. The mitigation from external to internal embedded sensing and its potential benefits/impacts to the performance of battery system, as well as the general requirement for sensor design and integration, are discussed systematically. Considering the design innovation and data transmission burden, the potential change of system-level smart battery integration is further discussed as an open outlook. •The development of smart battery system is overviewed.•Advanced sensing techniques for LIB multi-dimensional measurement are reviewed.•LIB management methods using multi-dimensional measurements are reviewed.•The integration of smart battery system and associated challenges are discussed.